Sternal resections Technique used - Tarabochia, Carlos; Pertusso, Juan C; Pertusso, P; Martínez, José L (Cirugía del Uruguay, 1995)
The authors present two cases of primitive tumors of the sternum which were treated by means of extensive resections. Parietal defects which were situated in the upper third in one case and the /ower one in the other, were repaired with a "sandwich" made of Mar/ex and methylmatacrilate with an epiploon covering. This combination made possible a good anatomica/, cosmetic and functional result, with a reasonable protection against infections